Preconcentration and Determination of Fe(III) from Water and Food Samples by Newly Synthesized Chelating Reagent Impregnated Amber lite XAD-16 Resin - Tokalioglu, Serife; Ergun, Hasan; Cukurovali, Alaaddin (Wiley-V C H Verlag Gmbh, 2010)
A simple and reliable method has been developed to selectively separate and concentrate trace amounts of Fe(III) ions from water and food samples by using flame atomic absorption spectrometry. A new reagent, 5-hydroxy-4-ethyl-5,6-di-pyridin-2-yl-4,5-dihydro-2H-[1,2,4] triazine-3-thione, was synthesized and characterized by using FT-IR spectroscopy and elemental analysis. Effects of pH, concentration and volume of elution solution, sample flow rate, sample volume and interfering ions on the recovery of Fe(III) were investigated. The optimum pH was found to be 5. Eluent for quantitative elution was 10 mL of 2 M HCl. The preconcentration factor of the method, detection limit (3s/b, mu g L-1) and relative standard deviation values were found to be 25, 4.59 and 1%, respectively. In order to verify the accuracy of the method, two certified reference materials (TMDA 54.4 lake water and SRM 1568a rice flour) were analyzed. The results obtained were in good agreement with the certified values. The method was successfully applied to the determination of Fe(III) ions in water and food samples.
Keywords: Fe(III); Solid phase extraction; A new reagent; Flame atomic absorption spectrometry